13. STRESSORS AND COPING STRATEGIES AMONG NURSING STUDENTS AT NGUYEN TAT THANH UNIVERSITY DURING CLINICAL TRAINING IN HO CHI MINH CITY (Vietnam Journal of Community Medicine, 2024)
Objective: To describe the level of stress characteristics, coping capacity and related factors of nursing students at Nguyen Tat Thanh University participating in clinical training in Ho Chi Minh City. Methods: A cross-sectional descriptive study of 509 nursing students who participated in caring for patients in Ho Chi Minh City from 12/2022 to 09/2023. The Perceived Stress Scale (PSS) and the Coping Behavior Inventory (CBI) are reliable and valid tools used in the literature. Results: The study’s results showed that the average score was 1.98±0.43. The hospital environment (2.53±0.93) was a significant source of stress. The most common coping behaviour during their initial clinical experience was transference (3.06±0.86). There was a difference between the stress levels from lack of professional knowledge and skills, and problem-solving reported coping strategy between the third-year and senior-year nursing students (p < 0.05). Conclusions: The overall value of the PSS suggested moderate stress levels. Lack of professional knowledge and employed problem-solving were the significant sources of stress and coping strategies during the initial period of clinical practice. Therefore, arranging reasonable time for theoretical and practical lectures, psychological and professional support for nursing students, and cooperating in building practical policies between schools and hospitals are necessary activities in the clinical teaching process in the future.
Keywords: Stress, clinical training, nursing students.